2006
DOI: 10.1143/jjap.45.8484
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recrystallization of Amorphous Silicon Utilizing Very-High-Frequency Microplasma Jet at Atmospheric Pressure

Abstract: The absolute flux of a femtosecond vacuum-ultraviolet (VUV) photon source based on the high-order harmonic generation of a femtosecond Ti:sapphire laser and monochromatized with a grating monochromator is determined both on a shot-to-shot basis and averaged over seconds by a calibrated gas monitor detector. The average flux is compared with the average flux as determined with a calibrated GaAsP semiconductor photodiode. We found that the photodiode is a reliable and easy-to-use tool for estimating the order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Atmospheric pressure plasma technology is advantageous in versatile applications including surface modification, rapid thermal annealing, thin-film deposition, bacteria inactivation, and rapid sintering processes. , Atmospheric pressure plasma jet (APPJ) processes involve the reaction chemistry in the nonthermal plasmas; the participation of oxygen atoms in the plasmas can effectively remove organics by oxidation, rendering rapid processing capability. ,, In addition, it is a nonvacuum process that is compatible with large-area and roll-to-roll fabrication. , Atmospheric pressure plasmas (APPs) have been used in many aspects of solar cell fabrication. A 30 min radio frequency (rf) APP has been used for the preparation of TiO 2 photoanodes of on-plastic DSSCs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric pressure plasma technology is advantageous in versatile applications including surface modification, rapid thermal annealing, thin-film deposition, bacteria inactivation, and rapid sintering processes. , Atmospheric pressure plasma jet (APPJ) processes involve the reaction chemistry in the nonthermal plasmas; the participation of oxygen atoms in the plasmas can effectively remove organics by oxidation, rendering rapid processing capability. ,, In addition, it is a nonvacuum process that is compatible with large-area and roll-to-roll fabrication. , Atmospheric pressure plasmas (APPs) have been used in many aspects of solar cell fabrication. A 30 min radio frequency (rf) APP has been used for the preparation of TiO 2 photoanodes of on-plastic DSSCs .…”
Section: Introductionmentioning
confidence: 99%
“…Improved performance of DSSCs with TiO 2 treated by atmospheric-pressure nonequilibrium direct current (DC) pulse discharge plasma jet , and DBD-treatment have been demonstrated. Atmospheric pressure plasma TiO 2 coating was also suggested for the protection layer of plastic substrates for DSSCs. , In addition to the application of nonthermal-equilibrium plasmas to solar cell fabrication, some thermal-plasma techniques have been used for the annealing of ZnO:Al films and recrystallization of amorphous Si for Si thin-film solar cells. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Recently developed has been rapid thermal processing (RTP) for thin films, in which an ICP torch is used as a heat source. The ICP torch is scanned at high speed, and polycrystalline silicon film can be acquired by heating the α-Si film over a very short period of time, on the order of ms [30]. This process has advantages of lower tool costs and lower operating costs compared to laser annealing, with further improvements expected in the future.…”
Section: Future Prospects Of Icpmentioning
confidence: 99%
“…It has been reported that the ICP torch enables a-Si film crystallization. 34,35) The ICP torch is capable of large-area processing if an elongated thermal plasma is generated. Since the ICP torch uses no electrodes, there is no need to worry about contamination and heat source fluctuation.…”
Section: Introductionmentioning
confidence: 99%